Comparison of best supportive care, CHOP, or R-CHOP for treatment of diffuse large B-cell lymphoma in Malawi: a cost-effectiveness analysis. Issue 9 (September 2021) - Painschab, Matthew S; Kohler, Racquel; Kimani, Stephen; Mhango, Wilberforce; Kaimila, Bongani; Zuze, Takondwa; Mithi, Victor; Kasonkanji, Edwards; Mumba, Noel; Nyasosela, Richard; Wheeler, Stephanie; Gopal, Satish
Summary: Background: Cost-effectiveness data for cancer treatment are needed from sub-Saharan Africa, where diffuse large B-cell lymphoma (DLBCL) is a common, curable cancer. In high-income countries, the standard of care for DLBCL is R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone) chemoimmunotherapy. Rituximab is often not available in sub-Saharan Africa due to perceived unaffordability, and treatment with CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisone) is common. We aimed to evaluate the cost-effectiveness of treatment in Malawi, comparing best supportive care, CHOP, or R-CHOP in patients with DLBCL. Methods: For this cost-effectiveness analysis, we used published Malawi microcosting data, clinical data from a prospective cohort treated with CHOP, and clinical trial data evaluating R-CHOP. We used a decision-tree model to calculate costs per disability-adjusted life-year (DALY) averted from the health system perspective for the treatment of patients with DLBCL with best supportive care, CHOP, or R-CHOP, running the model on a per-patient basis and a Malawi population-level basis. We used the WHO definitions of cost-effective (three times the GDP per capita of the country) and extremely cost-effective (equal to the GDP per capita of the country) as willingness-to-pay thresholds for Malawi. Findings: On a per-patient level, compared with best supportive care, CHOP was estimated to avert a mean 7·4 DALYs at an incremental cost of US$1384, for an incremental cost-effectiveness ratio (ICER) of $189 per DALY averted, which is substantially lower than the willingness-to-pay threshold (extremely cost-effective). Compared with CHOP, R-CHOP was estimated to avert 2·8 DALYs at an incremental cost of $3324, resulting in an ICER of $1204 per DALY averted, which is slightly higher than the cost-effective willingness-to-pay threshold. In probabilistic sensitivity analyses, CHOP remained cost-effective for DLBCL treatment in more than 99% of simulations, whereas R-CHOP was lower than the threshold in 46% of simulations. Interpretation: We estimated CHOP to be cost-effective for DLBCL treatment in Malawi, and that the addition of rituximab might be cost-effective. Despite upfront costs, DLBCL treatment is probably a prudent investment relative to other accepted health interventions in sub-Saharan Africa. Funding: National Institutes of Health.